Induction of solid tumor differentiation by the peroxisome proliferator-activated receptor-γ ligand troglitazone in patients with liposarcoma - Demetri, George D. (The National Academy of Sciences, 1999)
Agonist ligands for the nuclear receptor peroxisome proliferator-activated receptor-γ have been shown to induce terminal differentiation of normal preadipocytes and human liposarcoma cells in vitro. Because the differentiation status of liposarcoma is predictive of clinical outcomes, modulation of the differentiation status of a tumor may favorably impact clinical behavior. We have conducted a clinical trial for treatment of patients with advanced liposarcoma by using the peroxisome proliferator-activated receptor-γ ligand troglitazone, in which extensive correlative laboratory studies of tumor differentiation were performed. We report here the results of three patients with intermediate to high-grade liposarcomas in whom troglitazone administration induced histologic and biochemical differentiation in vivo. Biopsies of tumors from each of these patients while on troglitazone demonstrated histologic evidence of extensive lipid accumulation by tumor cells and substantial increases in NMR-detectable tumor triglycerides compared with pretreatment biopsies. In addition, expression of several mRNA transcripts characteristic of differentiation in the adipocyte lineage was induced. There was also a marked reduction in immunohistochemical expression of Ki-67, a marker of cell proliferation. Together, these data indicate that terminal adipocytic differentiation was induced in these malignant tumors by troglitazone. These results indicate that lineage-appropriate differentiation can be induced pharmacologically in a human solid tumor.